Exploring the impact of lipid droplets on the evolution and progress of hepatocarcinoma - Maurotti, Samantha; Geirola, Nadia; Frosina, Miriam; Mirarchi, Angela; Scionti, Francesca; Mare, Rosario; Montalcini, Tiziana; Pujia, Arturo; Tirinato, Luca (Frontiers in Cell and Developmental Biology, 2024)
Over the past ten years, the biological role of lipid droplets (LDs) has gained significant attention in the context of both physiological and pathological conditions. Considerable progress has been made in elucidating key aspects of these organelles, yet much remains to be accomplished to fully comprehend the myriad functions they serve in the progression of hepatic tumors.Our current perception is that LDs are complex and active structures managed by a distinct set of cellular processes. This understanding represents a significant paradigm shift from earlier perspectives.In this review, we aim to recapitulate the function of LDs within the liver, highlighting their pivotal role in the pathogenesis of metabolic-associated fatty liver disease (MAFLD) metabolic dysfunctionassociated steatotic liver disease (MASLD) [1] and their contribution to the progression towards more advanced pathological stages up to hepatocellular carcinoma (HC). We are aware of the molecular complexity and changes occurring in the neoplastic evolution of the liver. Our attempt, however, is to summarize the most important and recent roles of LDs across both healthy and all pathological liver states, up to hepatocarcinoma. For more detailed insights, we direct readers to some of the many excellent reviews already available in the literature [2][3][4][5].